2022
DOI: 10.1161/jaha.121.023274
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization in the Perivascular Fat Was Associated With Coronary Atherosclerosis

Abstract: Background Inflammation of the perivascular adipose tissue (PvAT) may be related to atherosclerosis; however, the association of polarized macrophages in the pericoronary PvAT with measurements of atherosclerosis components in humans has not been fully investigated. Methods and Results Coronary arteries were dissected with surrounding PvAT. We evaluated the percentage of arterial obstruction, intima‐media thickness, fibrous cap thickness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
11

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 46 publications
1
16
0
11
Order By: Relevance
“…In obesity, inflammation in PVAT causes the phenotypic switch from anti-inflammatory to pro-inflammatory [ 69 ]. A recent study has also revealed that macrophage polarization in the PVAT is critically associated with coronary atherosclerosis [ 70 ]. M1 macrophages in the PVAT are positively correlated with a higher risk of coronary thrombosis and are correlated with plaque progression and destabilization.…”
Section: What Is the Function Of Pvat?mentioning
confidence: 99%
See 1 more Smart Citation
“…In obesity, inflammation in PVAT causes the phenotypic switch from anti-inflammatory to pro-inflammatory [ 69 ]. A recent study has also revealed that macrophage polarization in the PVAT is critically associated with coronary atherosclerosis [ 70 ]. M1 macrophages in the PVAT are positively correlated with a higher risk of coronary thrombosis and are correlated with plaque progression and destabilization.…”
Section: What Is the Function Of Pvat?mentioning
confidence: 99%
“…M1 macrophages in the PVAT are positively correlated with a higher risk of coronary thrombosis and are correlated with plaque progression and destabilization. M2 macrophages in the PVAT are negatively correlated with increased arterial obstruction, calcification, necrosis, and decrease of the number of vasa vasorum in the adventitia layer [ 70 ]. Transplantation of PVAT from high-cholesterol diet-fed apolipoprotein E (ApoE) knockout mice to normal chow-fed ApoE-knockout mice resulted in a striking increase in atherosclerosis development [ 71 ].…”
Section: What Is the Function Of Pvat?mentioning
confidence: 99%
“…A discussão da investigação dos macrófagos polarizados no TAP periplaca com a aterosclerose coronariana já foi previamente realizada e publicada em artigo científico apresentado no capítulo de resultados. 137 Aqui discutiremos os resultados da associação entre o perfil inflamatório dos linfócitos T e a aterosclerose em artérias coronárias.…”
Section: Discussionunclassified
“…Foi realizado testes de concordância entre o processamento automático em relação ao manual e obtivemos uma taxa de 94% para a LLEI (Figura 35) e para o lúmen (Figura 36). 137,138 As artérias que apresentaram alterações de contornos devido ao processamento delicado da histologia (deformações ou rompimentos) foram realizadas manualmente. As principais vantagens em relação ao processamento manual executado por um pesquisador compreendem: menor tempo de execução por se tratar de processamento em tempo de máquina; reprodutibilidade e maior precisão por não haver divergências nos resultados se utilizados os mesmos critérios e o mesmo material, além da possibilidade de uma ferramenta dedicada para a tarefa (em substituição ao software Image J ® que era utilizado para as mensurações).…”
Section: Avaliação Macroscópicaunclassified
See 1 more Smart Citation